KOMPOSISI DAN KEANEKARAGAMAN JENIS POHON DI KAWASAN IZIN USAHA PERTAMBANGAN PT. ANTAM UBPE PONGKOR, BOGOR - Setyaningsih, Luluk; Silaturahmi, Silaturahmi; Mulya, Hanjar; Rusli, Abdul Rahman; Habib, Syaiful (Jurnal Nusa Sylva, 2022)
Post-mining land revegetation is one of PT. ANTAM UBPE Pongkor committed to restoring the impact of both mining and non-mining activities in its concession area, comprising 3 locations (GHSNP Critical Land, Cepu Landslide Block, and Mount Puntang Block). This study aimed to identify the species composition, diversity, evenness, and richness of tree species. This research was carried out by observation at 12 locations following checkered paths, parallel to intersecting contour lines. Observation sample plots for the tree, pole, sapling, and seedling were measured on areas 20x20 m, 10x10 m, 5x5 m, and 2x2 m, respectively, with maximum sampling intensity of 10%. Vegetation composition and structure were observed by measuring the Importance Value Index (IVI), the Biodiversity Index (H'), Species Evenness Index, and Richness Index (Dmg). Sixty species of trees were found in the IUP area of PT. ANTAM UBPE Pongkor, in the growth phase of trees, saplings, poles, and seedlings, dominated by Puspa, Rasamala, Waru Lot Mara, Calik Angin, Huru, Kaliandra, and Ganitri, which were spread almost evenly in each location, with IVI value of 50% -300 %. Species diversity with a high category (H' =3.23) was found in the natural forest in the Baching Plant, the medium category was in the cepu landslide block reclamation area (2.67), while the small diversity was in the reclamation area around the administration office (1.61). The evenness index (E) ranged from 0 to 1, and the species richness index (Dmg) ranged from 0 – 7.58, indicating that the IUP area is quite diverse regarding its biodiversity.